2010
DOI: 10.1103/physrevb.82.205103
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure theory of the hidden-order materialURu2Si2

Abstract: We report a comprehensive electronic structure investigation of the paramagnetic ͑PM͒, the large moment antiferromagnetic ͑LMAF͒, and the hidden order ͑HO͒ phases of URu 2 Si 2 . We have performed relativistic full-potential calculations on the basis of the density-functional theory, employing different exchangecorrelation functionals to treat electron correlations within the open 5f shell of uranium. Specifically, we investigate-through a comparison between calculated and low-temperature experimental properti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
151
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(179 citation statements)
references
References 147 publications
(330 reference statements)
28
151
0
Order By: Relevance
“…The transition results in a folding of the Brillouin zone through a commensurate vector Q which is consistent with Angle Resolved Photoemission [12], de Haasvan Alphen [13] and neutron scattering measurements [14]. Similar nesting conditions have been found to be satisfied in LDA calculations [15,16] of the electronic structure of URu 2 Si 2 . We have shown [9] that the transition in the underscreened Anderson Lattice Model can be considered as resulting in a coupled spin and orbital density wave such that the orbital density wave for the spin-up is exactly out of phase with the orbital density wave for the spin-down electrons.…”
Section: Introductionsupporting
confidence: 81%
“…The transition results in a folding of the Brillouin zone through a commensurate vector Q which is consistent with Angle Resolved Photoemission [12], de Haasvan Alphen [13] and neutron scattering measurements [14]. Similar nesting conditions have been found to be satisfied in LDA calculations [15,16] of the electronic structure of URu 2 Si 2 . We have shown [9] that the transition in the underscreened Anderson Lattice Model can be considered as resulting in a coupled spin and orbital density wave such that the orbital density wave for the spin-up is exactly out of phase with the orbital density wave for the spin-down electrons.…”
Section: Introductionsupporting
confidence: 81%
“…We performed two types of calculations, with and without spin-orbit coupling (SOC), assuming in both cases the non-magnetic ground state. The optimized lattice parameters show good agreement with the experimental values and the previous relativistic full-potential calculations 55 .…”
Section: Theoretical Calculations Of Phonon Dispersion Curvessupporting
confidence: 76%
“…Their enhanced effective masses (m * = 8 − 25m 0 ) 7,8 cannot adequately be described by band structure calculations (m b ≤ 8m 0 ) 7 although the latter give a Fermi surface sheet topology in agreement with dHvA and SdH experiments 1,6 . Conceptually mass enhancement can be obtained within the Anderson lattice model in constrained mean field approximation 38 which also leads to a narrow indirect hybridization gap close to the Fermi level, equivalent to the Kondo temperature (T K 11.1 meV or 129 K) that can be seen in STM experiments 20,39 .…”
Section: Two Orbital Model For Hidden Order and Heavy Quasiparticmentioning
confidence: 91%
“…We rather model directly the heavy quasiparticle bands and their Fermi surface by a simple effective tight binding model. Ab-initio LDA calculations 6,17 have shown that states at the Fermi surface consist mostly of jj-coupled total angular mometum 5f states |j = . Therefore the heavy bands, which have twofold Kramers-pseudo spin degeneracy may be directly described within an effective two-orbital tight binding model due to Rau and Kee…”
Section: Two Orbital Model For Hidden Order and Heavy Quasiparticmentioning
confidence: 99%
See 1 more Smart Citation